2013
DOI: 10.1016/j.jvir.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Respiration-induced Deformations of the Superior Mesenteric and Renal Arteries in Patients with Abdominal Aortic Aneurysms

Abstract: Purpose This study was performed to quantify respiration-induced deformations of the superior mesenteric artery (SMA) and left and right renal arteries (LRA and RRA) in patients with small abdominal aortic aneurysms (AAA). Materials and Methods Sixteen men with AAAs (73±7 years) were imaged with contrast-enhanced magnetic resonance angiography during inspiratory and expiratory breath-holds. Centerline paths of the aorta and the visceral arteries were acquired by geometric modeling and segmentation techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…The RRA was in contact with the IVC 20 to 34-mm distal to the aorta, explaining why the RRA translated significantly less than the LRA at the 30-mm point (P≤ 0.03) due to respiration. This evidence supports previous findings that the IVC’s contact with the RRA provides mechanical support [10,12]. Due to this combination of characteristics, the RRA translation within the proximal 30-mm of length appears to be less correlated to kidney translation as compared to the LRA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The RRA was in contact with the IVC 20 to 34-mm distal to the aorta, explaining why the RRA translated significantly less than the LRA at the 30-mm point (P≤ 0.03) due to respiration. This evidence supports previous findings that the IVC’s contact with the RRA provides mechanical support [10,12]. Due to this combination of characteristics, the RRA translation within the proximal 30-mm of length appears to be less correlated to kidney translation as compared to the LRA.…”
Section: Discussionsupporting
confidence: 89%
“…Such endovascular techniques are effective at preserving target vessel patency initially, but longer-term studies have identified the potential for branch vessel stent-graft instability and renal compromise using either technique, potentially as a result of branch graft dislodgement, migration, or kinking [810]. These long-term limitations highlight the need to quantify in vivo visceral vessel geometry and deformation as a function of diaphragmatic excursion and respiratory-related displacement of the abdominal viscera [1,1012]. …”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed to model human vessels and quantify geometric curvature. Classic methods have employed 2D level set segmentation creating a set of orthogonal contours following vascular lumen, acquiring centerlines from the contours, and computing the curvature along the centerline [ 6 , 7 , 21 , 22 , 24 , 25 ]. Other available methods include 3D segmentation with growing seeds, acquiring centerline from inscribing spheres in lumenal surface, and computing the centerline curvature [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal arteries become relatively straight during inspiration, but become more curved during expiration. 12 This cyclic bending exposes the bridging covered stents to mechanical stress. 12,13 In theory, the risk of stent failure can be minimized by avoiding long stents extending to the distal part of renal artery, where the arterial bending is greater than proximally.…”
Section: Discussionmentioning
confidence: 99%
“…12 This cyclic bending exposes the bridging covered stents to mechanical stress. 12,13 In theory, the risk of stent failure can be minimized by avoiding long stents extending to the distal part of renal artery, where the arterial bending is greater than proximally. However, the length of the covered stent in the renal artery was not a significant risk factor for occlusion.…”
Section: Discussionmentioning
confidence: 99%